Modelling of Time Efficiency in Heterogeneous and Adhoc Networks - Yatendra Singh Bhandari; Yashwant Singh Chauhan; Priti Dimri (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
Heterogeneous Networks are bunch of homogeneous networks base stations grouped together. The term introduced in this research paper Time Efficiency (Te) gives out the information on the heterogeneous networks where most of the data flows in and out. In this paper, a model for evaluating Time Efficiency in heterogeneous network is developed. The common goals of different base stations in a heterogeneous network are towards coverage of area and capability improvement. Base stations in a homogeneous network differs in transmitted power, achievable rate of data, area covered, density of a base station, energy efficiency and time efficiency. To find out the area of most data flow in certain period, Time efficiency can be used as a major factor.